2012
DOI: 10.1007/978-1-61779-764-4_13
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Vascular Analysis of Tissue Engineering Scaffolds, Part 2: Topology Optimisation

Abstract: Rapid prototyping technologies were recently introduced in the medical field, being particularly viable to produce porous scaffolds for tissue engineering. These scaffolds should be biocompatible, biodegradable, with appropriate porosity, pore structure, and pore distribution, on top of presenting both surface and structural compatibility. Surface compatibility means a chemical, biological, and physical suitability with the host tissue. Structural compatibility corresponds to an optimal adaptation to the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the field of tissue engineering, researchers are exploring AM to assemble biocompatible 3D scaffolds seeded with stem cells to assist bone repair (Seyednejad et al, 2012a). The promise of producing tissues and artificial organs is a rapidly growing area of research, visible in RP, RM and tissue engineering conferences and publications (Almeida et al, 2007;Almeida and Bártolo, 2012;Seyednejad et al, 2012b). This requires a variety of skills, knowledge and technologies (i.e.…”
Section: Biofabrication: Patient-specific Implants Scaffolds Livingmentioning
confidence: 99%
“…In the field of tissue engineering, researchers are exploring AM to assemble biocompatible 3D scaffolds seeded with stem cells to assist bone repair (Seyednejad et al, 2012a). The promise of producing tissues and artificial organs is a rapidly growing area of research, visible in RP, RM and tissue engineering conferences and publications (Almeida et al, 2007;Almeida and Bártolo, 2012;Seyednejad et al, 2012b). This requires a variety of skills, knowledge and technologies (i.e.…”
Section: Biofabrication: Patient-specific Implants Scaffolds Livingmentioning
confidence: 99%
“…[17] The latest generations of scaffolds have been engineered to have ideal properties and functional customization: injectability, synthetic manufacture, biocompatibility, nonimmunogenicity, transparency, nano-scale fibers, low concentration, and high resorption rates. [18] The types of scaffold materials available are natural or synthetic, biodegradable or permanent [19'20] Biological or natural scaffolds:-Blood clot:-The utilization of a blood clot to regenerate dental pulp tissues was first practiced by Ostby and resulted in a growth of granulation tissues, fibrous tissues or cementum-like tissues into the root canals. [21] It is believed that tissues are not able to grow into empty spaces with the absence of suitable scaffolds, [21] it can be suggested that blood clots yield good scaffolds to fill intracanal spaces and aid the growth of new tissues.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…Computer-Aided Design of Scaffolds (CADS) makes the bridge between different computer applications by allowing to material database tools (knowledge based systems for materials selection), CAD modelling systems, numerical simulation tools for structural, topological and fluid dynamics optimisation based on the Finite Element Method. Reviews of computer-aided design of scaffolds in tissue engineering can be found in "Structural and Vascular Analysis of Tissue Engineering Scaffolds: Part 1 -Numerical Fluid Analysis" [15], "Structural and Vascular Analysis of Tissue Engineering Scaffolds: Part 2 -Topology Optimization" [16] and "Computer-Aided Tissue Engineering" [17].…”
Section: Computer-aided Design Of Scaffolds (Cads)mentioning
confidence: 99%